Ial Maths p3 PEP
Ial Maths p3 PEP
Ial Maths p3 PEP
x2 − 9 2 x2 + 5x − 3 x2 − 9 x2 + 7 x
1 ÷ = ×
x 2 − 3x x2 + 7 x x 2 − 3x 2 x 2 + 5 x − 3
=
( x + 3)( x − 3) × x ( x + 7 )
x ( x − 3) ( 2 x − 1)( x + 3)
x+7
=
2x −1
c When V = 1400
800e −0.2t + 1000e −0.1t + 200 = 1400
−0.2 t −0.1t
800e + 1000e 1200
=
−0.2 t −0.1t
4e + 5e = 6
Let x = e −0.1t
4 x2 + 5x − 6 = 0
( 4 x − 3)( x + 2 ) = 0
3
x= or x = −2
4
3
Since x is positive x =
4
Therefore:
3
e −0.1t =
4
3
−0.1t = ln
4
3
t = −10 ln
4
4
= 10 ln
3
© Pearson Education Ltd 2019. Copying permitted for purchasing institution only. This material is not copyright free. 1
3 a f ( x=
) ( 4 − 3x ) e x
= 4e x − 3 xe x
f ′ ( x ) =4e x − ( 3e x + 3 xe x )
= e x − 3 xe x
= e x (1 − 3 x )
At the turning point f ′ ( x ) = 0
Therefore:
1
x=
3
1
At x =
3
1
1 3
f ( x=
) 4 − 3 e
3
1
= 3e 3
1 1
Therefore, the turning point lies at ,3e 3
3
1
b f ( x ) ≤ 3e 3
c f ( x=
) ( 4 − 3x ) e x
At x = 0, |f(x)| = 4
So the curve cuts the y-axis at (0, 4)
At f(x) = 0
( 4 − 3x ) e x =
0
( 4 − 3x ) e x =
0
4
x=
3
4
So the curve cuts the x-axis at , 0
3
© Pearson Education Ltd 2019. Copying permitted for purchasing institution only. This material is not copyright free. 2
4 a
© Pearson Education Ltd 2019. Copying permitted for purchasing institution only. This material is not copyright free. 3
f ( x ) 3sin 2 x + 2 cos 2 x
5 a=
=sin 2 x + 2sin 2 x + 2 cos 2 x
=sin 2 x + 2 ( sin 2 x + cos 2 x )
= sin 2 x + 2
1 − cos 2 x
= +2
2
1 − cos 2 x + 4
=
2
5 − cos 2 x
= as required
2
π π
5 − cos 2 x 1
4 4
∫ ( 5 − cos 2 x ) dx
2 ∫0
b = dx
0
2
π
1 1 4
= 5 x − sin 2 x
2 2
0
1 5π 1 π
= − sin − 0
2 4 2 2
1 5π 1
= −
2 4 2
5π 1
= −
8 4
5π − 2
=
8
π
6 a =
y x 2 + sin x
2
dy π π
= 2 x + cos x
dx 2 2
© Pearson Education Ltd 2019. Copying permitted for purchasing institution only. This material is not copyright free. 4
b At x = −1
π
( 1) + sin −
2
y =−
2
=0
dy π π
= 2 ( −1) + cos −
dx 2 2
= −2
1
Therefore, the normal has gradient
2
1
Using y − y1= m ( x − x1 ) with m = at (−1, 0) gives:
2
1
=y ( x + 1)
2
π
3k
7 π (7 − 6 2 )
∫ (1 − π sin kx ) dx =
π
4k
π π
3k
π 3k
∫π (1 − π sin kx ) dx =
x + k cos kx π
4k
4k
π π π π π π
= + cos − + cos
3k k 3 4k k 4
π π π π π π
= − + cos − cos
3k 4k k 3 k 4
π1 1 π π
= − + cos − cos
k 3 4 3 4
π 1 1 2
= + −
k 12 2 2
π 1 6 6 2
= + −
k 12 12 12
π7−6 2
=
k 12
π7−6 2
=
k 12
π 7−6 2 ( )
1 1
=1
k 12
1
k=
12
© Pearson Education Ltd 2019. Copying permitted for purchasing institution only. This material is not copyright free. 5
3 x3 − 10 x 2 + 8 x + 1
8 f ( x) =
x2 − 4 x + 4
3 x3 − 10 x 2 + 8 x + 1
=
( x − 2 )( x − 2 )
3 x3 − 10 x 2 + 8 x + 1 C D
= Ax + B + +
( x − 2 )( x − 2 ) x − 2 ( x − 2 )2
C ( x − 2 )( x − 2 ) D ( x − 2 )( x − 2 )
1 Ax ( x − 2 )( x − 2 ) + B ( x − 2 )( x − 2 ) +
3 x3 − 10 x 2 + 8 x += +
( x − 2)
2
x−2
= Ax ( x − 2 )( x − 2 ) + B ( x − 2 )( x − 2 ) + C ( x − 2 ) + D
= A ( x3 − 4 x 2 + 4 x ) + B ( x 2 − 4 x + 4 ) + C ( x − 2 ) + D
Comparing coefficients
For x3:
A=3
For x2:
−4 A + B = −10
−4 ( 3) + B =−10
B=2
For x:
4 A − 4B + C = 8
4 ( 3) − 4 ( 2 ) + C =
8
12 − 8 + C =8
C=4
Therefore:
3 x3 − 10 x 2 + 8 x + 1 4 1
= 3x + 2 + +
( x − 2 )( x − 2 ) x − 2 ( x − 2 )2
© Pearson Education Ltd 2019. Copying permitted for purchasing institution only. This material is not copyright free. 6
1
( x)
9 a f= +3
4− x
1
( 3.9 )
f= +3
4 − 3.9
= 13
1
( 4.1)
f= +3
4 − 4.1
= −7
1 4 x +3
∫ e=
4 x +3
10 a dx e +c
4
© Pearson Education Ltd 2019. Copying permitted for purchasing institution only. This material is not copyright free. 7
cos 4 x
10 b ∫ esin 4 x
dx
Let u = sin 4 x
du
= 4 cos 4 x ⇒= du 4 cos 4 x dx
dx
cos 4 x 1 1
∫ esin 4 x dx = 4 ∫ eu du
1
= ∫ e − u du
4
1
= − e−u + c
4
1
= − e − sin 4 x + c
4
© Pearson Education Ltd 2019. Copying permitted for purchasing institution only. This material is not copyright free. 8